Control interno y su incidencia en la productividad de la lubricadora “Los Àlamos” cantón La Mana, año 2021 - Esquivel Garcìa, Glenda Marisela (2021)
During this investigation, an “Internal control and its impact on the productivity of the Los Alamos canton La Maná year 2021” will be carried out. It should be mentioned that in the company it is necessary to improve each of the administrative and financial controls processes, through strategies Its main purpose is to apply policies, regulations and procedures and at the same time to implement a series of resources such as function manuals, an inventory control system, training and motivation for workers since it can be realized that this is what is missing for the company to become profitable. The objective is to contribute with the owners in the activities of the company through the study of a diagnosis of the control that is taking place in the Lubricator, it will be possible to design policies and procedures making sure that from these changes positive effects arise within the administrative area. In Los Alamos lubricator, after the analysis, several alternatives to improve efficiency and productivity have been presented, so it has been considered that people are the link between the company and its customers, so there is a need to improve the productive process so that each worker is more efficient in the activities they carry out within the company. It has been possible to detect several shortcomings within the internal and external environment of the company, so it seeks to eradicate those deficiencies that do not allow an adequate development of the business, which is leading the company towards an inefficient profitability